Trail Making contributes to subjective judgment of visual efficiency in older adults - Setti,Annalisa; Loughman,James; Savva,George M; Kenny,RoseAnne (PeerJ PrePrints, 2015)
Introduction: The determinant factors that influence self-reported quality of vision have yet to be fully elucidated. This study evaluated a range of contextual information, established psychophysical tests, and in particular, a series of cognitive tests as potentially novel determinant factors. Materials & Methods: Community dwelling adults (aged 50+) recruited to Wave 1 of The Irish Longitudinal Study on Ageing, excluding those registered blind, participated in this study (N=5021). Self-reports of vision were analysed in relation to visual acuity and contrast sensitivity, ocular pathology, visual (Choice Response Time task; Trail Making Test) and global cognition. Contextual factors such as having visited an optometrist and wearing glasses were also considered. Ordinal logistic regression was used to determine univariate and multivariate associations. Results and Discussion: Poor Trail Making Test performance (Odds ratio, OR= 1.36), visual acuity (OR =1.72) and ocular pathology (OR=2.25) were determinant factors for poor versus excellent vision in self-reports. Education, wealth, age, depressive symptoms and general cognitive fitness also contributed to determining self-reported vision. Conclusions: Trail Making Test contribution to self-reports may capture higher level visual processing and should be considered when using self-reports to assess vision and its role in cognitive and functional health.
Keywords: visual search; visual acuity; self-report; ocular pathology; trail making test